Spatial Digital Twins for Port Concrete Pavements: A Theoretical Framework and Practical Insights - Tsaimou, Christina; Tsoukala, Vasiliki (Technical Annals, 2024)
Ports are critical infrastructure assets that play a key role in the functional and spatial activities related to maritime transportation. In today's digital age, the creation of Digital Twins (DTs) of port systems has become increasingly important in order to proactively address maritime issues. While port DTs are primarily used for logistics and operation, DT technologies can also aid in managing the performance of port infrastructure over its lifespan. This study presents a conceptual framework for developing Spatial Digital Twins (SDTs) of port concrete pavements at mooring facilities using Structural Health Monitoring (SHM) data. The framework incorporates Non-Destructive Testing (NDT) techniques including Ground Penetrating Radar (GPR), Falling Weight Deflectometer (FWD), and Unmanned Aerial Vehicle (UAV) camera-based methods. Moreover, Geographic Information Systems (GIS) tools are also employed to facilitate the creation of digital replicas using geospatial information. A contextualization of a UAV-driven application is presented for the concrete pavements of a Greek port, specifically Lavrio port with a focus on digitally representing structural surface defects, particularly cracking, with computer vision-based techniques. By showcasing how Spatial Digital Twins enable real-time representations of port concrete pavements, this study is valuable for understanding maintenance needs and offers practical insights for digital twin applications in port infrastructure management.